Alteration of Iron, Zinc, Vitamin A Breast Milk Levels During Lactation Period Among Mothers of Low Birth Weight Infant Born at Preterm and Term - Rizky Arisanti Maharani; Roedi Irawan; Risa Etika (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Duration of lactation and preterm delivery were noticed as dominant factors affecting breast milk composition, including its micronutrient particularly iron, zinc and vitamin A. This study was to analyze the alteration of iron, zinc, vitamin A levels within colostrum and mature breast milk among mothers of low birth weight (LBW) preterm and term infants.Methods: This cross-sectional study was conducted between July 2019 and April 2020 among mothers of LBW infant delivered at preterm and term at Dr. Soetomo hospital. Seventeen samples of breast milk were enrolled on each group. Respectively, colostrum and mature milk were collected between day 2 and 4, between day 15 and 20 after delivery.Results: The iron levels on both groups did not change significantly during lactation period (respectively p=0,266 and p=0,845). Zinc levels were found significantly higher in colostrum of both groups, as well as vitamin A levels within colostrum in LBW preterm group (p<0,05).Conclusions: Higher levels were found in zinc within colostrum of both groups, similar to vitamin A in LBW preterm group. In contrast, iron did not differ significantly during lactation period.